A novel inhibitor of signal transducers and activators of transcription 3 activation is efficacious against established central nervous system melanoma and inhibits regulatory T cells - Abou-Ghazal, Mohamed (2008)
Purpose: Activation of signal transducers and activators of transcription 3 (STAT3) has been identified as a central mediator of melanoma growth and metastasis. We hypothesized that WP1066, a novel STAT3 blockade agent, has marked antitumor activity, even against the melanoma metastasis to brain, a site typically refractory to therapies. Experimental Design: The antitumor activities and related mechanisms of WP1066 were investigated both in vitro on melanoma cell lines and in vivo on mice with subcutaneously syngeneic melanoma or with intracerebral melanoma tumors. Results: WP1066 achieved an IC50 of 1.6, 2.3, and 1.5 μmol/L against melanoma cell line A375, B16, and B16EGFRvIII, respectively. WP1066 suppressed the phosphorylation of Janus-activated kinase 2 and STAT3 (Tyr705) in these cells. Tumor growth in mice with subcutaneously established syngeneic melanoma was markedly inhibited by WP1066 compared with that in controls. Long-term survival (>78 days) was observed in 80% of mice with established intracerebral syngeneic melanoma treated with 40 mg/kg of WP1066 in contrast to control mice who survived for a median of 15 days. Although WP1066 did not induce immunologic memory or enhance humoral responses to EGFRvIII, this compound reduced the production of immunosuppressive cytokines and chemokines (transforming growth factor-β, RANTES, MCP-1, vascular endothelial growth factor), markedly inhibited natural and inducible Treg proliferation, and significantly increased cytotoxic immune responses of T cells. Conclusions: The antitumor cytotoxic effects of WP1066 and its ability to induce antitumor immune responses suggest that this compound has potential for the effective treatment of melanoma metastatic to brain.